Permanent education, health promotions strategy and personal project reformulation - Canal, Marina Elvira (2005)
Fil: Bravetti, Gabriela Rosana. Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación; Argentina.